Desain Roda Bersirip Standar dan Bersirip Buka Tutup untuk Pengujian di Lahan Sawah - Susanto, Herdi; Jayadi, Farid; Fathi, Syahrul; Marbun, Mahmuddin; Munawir, Al; Hasdi, Syaiful (universitas teuku umar, 2024)
The finned drive wheel technology is widely used for wet rice fields. Currently, finned drive wheels for peat fields have not been developed and still use traditional agricultural tools such as hoes and sickles, while the finned drive wheels for wet rice fields are not yet able to work optimally on peat rice fields. The driving wheel model and testing in peat rice fields were carried out in this research. Design and manufacturing were carried out by referring to previous research literature. This initial research was carried out in wet rice fields on open-close finned drive wheels and standard finned wheels, with the aim of measuring the comparative level of performance of the two wheel models. The wheel performance measured is sinkage and wheel rotational speed. The research produced two models of driving wheels, namely the standard fin type with a driving wheel diameter of 35 cm and a number of 8 fins and the open-close fin type producing a driving wheel diameter of 40 cm with 4 arcuate fins on the top surface of the driving wheel. Standard fin type drive wheels have smaller sinkage (11% on average) compared to open-close fin type wheels. The finned drive wheel with the open-close type has an average speed level that is 27.7% higher when compared to the standard finned type.Keywords – wheel drive, standard fins, open-close fins, sinkage, wheel speed